Endosymbiotic microorganisms of scale insects - Rosenblueth, Mónica; Martínez-Romero, Julio; Ramírez-Puebla, Shamayim Tabita; Vera-Ponce de León, Arturo; Rosas-Pérez, Tania; Bustamante-Brito, Rafael; Rincón-Rosales, Reiner; Martínez-Romero, Esperanza (TIP Revista Especializada en Ciencias Químico-Biológicas, 2017)
The evolutionary and ecological success of insects is largely due to their associated bacteria and fungi that expand their metabolic capacities or allow them to resist stress or parasites. Some of these associations possibly originated hundreds of millions of years ago and have resulted in such interdependence that in some cases the insect and bacteria may not exist separately. This has also led to a significant reduction in the genome size of bacterial symbionts and to the maternal transfer of symbionts to progeny. The study of insect symbionts has recently gained great interest and some of the biological functions of symbionts within hosts have been identified. Scale insects or cochineals feed on the sap of plants, which is rich in carbon but poor in nitrogen and so they require symbionts to compensate for diet deficiencies. Some scale insects are devastating crop pests. In this article, we review the symbionts of some scale insects focusing on carmine- and wax cochineals, which have commercial, art and craft interest. In the cochineals studied we found diverse microbial communities that can synthesize amino acids, vitamins, fix nitrogen or recycle the waste products of nitrogen metabolism.